FLORA DIVERSITY AND RESTORATION PLANNING FOR CRITICAL LAND IN STEAM-ELECTRIC POWER STATION ULUBELU AREAS - Munawaroh, Khoryfatul; Tohir, Rizki Kurnia; Sari, Nurika Arum; Jayani, Faradila Mei; Hasibuan, Mhd Muhajir; Kusuma, Andreas (Jurnal Belantara, 2025)
Geothermal Power Plants are one of the geothermal energies that can be used as a source of electricity. One of the geothermal powers in Lampung is the Ulubelu PLTP located in Tanggamus Regency. As an energy-producing agency, Ulubelu PLTP also contributes to preserving flora and fauna in their work area. This is shown through the planting of several types of wood plants to improve the flora in their work area. This study aims to record the types of plants that exist, the abundance of their types, climatic and edaphic factors, as well as recommendations for types that can be used for the enrichment of flora types in the Ulubelu PLTP work area. The vegetation analysis method used to collect flora data is a census method divided into 5 observation lines. The dominant and codominant types found at the tree level are Acacia mangium and Erythrina variegata, at the pole level Leucaena leucocephala and Toona sureni, at the pile level Gliricidia sepium and Syzygium myrtifolium, and at the lower plant level are Imperata cylindrica and Mikania micrantha. In addition to commercial types, some types have the potential to be invasive in the Ulubelu PLTP. The study also recommends that plant species be restored to increase species diversity and vegetation density. The types recommended for restoration based on vegetation analysis data are those that have aesthetic value, those that produce fruit or flowers that can present animals, and the protected types or types that can be used in addition to their wood.